Modified glass fiber, PFA composite material and preparation method thereof

By surface treatment of glass fibers and adding perfluorosilane and organic resin monomers to the fluororesin, the modified glass fibers are formed, which solves the problem of phase separation between glass fibers and fluororesin matrix, and significantly improves the mechanical properties and heat resistance of the material.

CN119191730BActive Publication Date: 2025-03-11JIHUA LAB
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411704961.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-11
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The existing glass fiber reinforced phase has serious phase separation problems when mixed directly with the fluororesin matrix, resulting in poor mechanical properties and heat and wear resistance of the material.

Method used

By deslurrying and etching the glass fibers with acidic solution, activated glass fibers are formed, and perfluorosilane and organic resin monomer are added to the resin reaction solution, and modified glass fibers are formed after heat treatment to improve the interface bonding force with the PFA composite material.

Benefits of technology

It effectively improves the phase separation problem during blending and doping of traditional composite materials, and significantly improves the mechanical properties and heat resistance of glass fiber reinforced PFA composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191730B_ABST
    Figure CN119191730B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of composite materials, and discloses a modified glass fiber, a PFA composite material and a preparation method thereof. The preparation method of the modified glass fiber comprises the following steps: desizing the glass fiber, etching it with an acid solution, washing it to neutrality and drying it to obtain an activated glass fiber; preparing a resin reaction liquid; adding perfluorosilane and the activated glass fiber to the resin reaction liquid and stirring it, separating the activated glass fiber and performing a heat treatment to obtain a modified glass fiber. The present application coats the surface of the glass fiber with an organic resin layer after roughening the surface. The organic resin layer has excellent elastic modulus and heat resistance, and can form a porous organic interface layer. The addition of perfluorosilane improves the interface lubricity, which can help melt and mechanically anchor with PFA, comprehensively improve the possible phase separation problem of traditional composite materials during blending and doping, and can also significantly improve the mechanical properties of glass fiber reinforced PFA composite materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite materials, and mainly to a modified glass fiber, PFA composite material and a preparation method thereof. Background Art

[0002] Fluororesin is a type of thermoplastic resin containing fluorine atoms in its molecular structure. The main varieties include PTFE (polytetrafluoroethylene), PVDF (polyvinylidene fluoride), PFA (tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer), ETFE (ethylene-tetrafluoroethylene copolymer), ECTFE (ethylene-chlorotrifluoroethylene copolymer), etc. Fluororesin and its derivatives have excellent high and low temperature resistance, corrosion resistance, non-stickiness and extremely low friction coefficient. They are widely used in aerospace, automobile, electronics and other fields that require precision. Among them, fluororesin composite materials reinforced with engineering plastics, fibers, metal oxides and other materials have broad application prospects.

[0003] The bonding strength of the interface layer of composite materials has long been a research focus, and it is necessary to make an adaptive solution in combination with different reinforcing phases and matrices. In recent years, the research on glass fiber (glass fiber) reinforced resin has entered a new stage of development. The most widely used and mature method for improving the interfacial bonding strength of glass fiber in industry is surface treatment with coupling agent. The sizing agent used in the glass fiber manufacturing process is often composed of water-based resin film-forming agent, lubricant, coupling agent and other additives, which can adapt to common resins such as polyester and polyolefin. However, conventional glass fiber treatment has the problems of poor wettability and poor heat resistance when applied to fluororesin matrix. It cannot be adapted to fluororesins with high molding temperature and harsh application conditions. In addition, if the composition is composed of fluororesin matrix, glass fiber reinforcement phase, PPS / POM / PEI / PI reinforcement phase, and molybdenum disulfide / graphite lubricating phase, the separation of phases is particularly serious. Therefore, it is necessary to design an interface modification method to make glass fiber reinforced fluororesin composites have better mechanical properties and heat and wear resistance. Therefore, the existing technology still needs to be improved and developed. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a modified glass fiber, PFA composite material and a preparation method thereof, aiming to solve the problem of severe phase separation when the existing glass fiber reinforcement phase is directly mixed with a fluororesin matrix.

[0005] The technical solution of this application is as follows:

[0006] In a first aspect, the present application provides a method for preparing a modified glass fiber, comprising the following steps:

[0007] The glass fiber is desized, and then etched with an acid solution, washed to neutrality, and then dried to obtain activated glass fiber;

[0008] Preparing a resin reaction solution;

[0009] Perfluorosilane and the activated glass fiber are added to the resin reaction solution and stirred, and the activated glass fiber is separated and then heat-treated to obtain modified glass fiber.

[0010] Through the preparation method provided in the present application, the glass fiber surface is roughened and then coated with an organic resin layer. The organic resin layer has excellent elastic modulus and heat resistance, and can form a porous organic interface layer. The addition of perfluorosilane can improve the interface lubricity, which can help to melt and mechanically anchor with PFA, comprehensively improve the phase separation problem during blending and doping of traditional composite materials, and can also significantly improve the mechanical properties of glass fiber reinforced PFA composite materials.

[0011] Furthermore, the step of preparing the resin reaction solution comprises:

[0012] Adding diamine monomer and dianhydride monomer into a solvent, and reacting under nitrogen protection to obtain a precursor solution;

[0013] Then, dibutyl phthalate is added into the precursor solution and stirred to obtain the resin reaction solution.

[0014] Furthermore, the heat treatment step comprises:

[0015] The activated glass fiber is first kept at 80-150° C. for 30-50 minutes, then kept at 150-220° C. for 40-60 minutes, and finally kept at 280-340° C. for 20-40 minutes.

[0016] Further, the mass of the precursor generated by the reaction of the diamine monomer and the dianhydride monomer is 10-13% of the mass of the solvent;

[0017] The mass proportion of dibutyl phthalate in the resin reaction liquid is 5-8%;

[0018] The diamine monomer is one or more of 2,2'-bis(trifluoromethyl)diaminobiphenyl, 4,4'-diaminodiphenyl ether, p-phenylenediamine, and 2-(4-aminophenyl)-5-aminobenzimidazole;

[0019] The dianhydride monomer is one or more of 4,4'-diphenyl ether tetracarboxylic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, and hexafluoroisopropylphthalic anhydride;

[0020] The solvent is one or more of dimethylacetamide, dimethylformamide and methyl pyrrolidone.

[0021] Furthermore, the added mass of the activated glass fiber is 10-15% of the mass of the resin reaction solution;

[0022] The added mass of the perfluorosilane is 2-3% of the mass of the activated glass fiber;

[0023] The perfluorosilane is one or more of 1H,1H,2H,2H-perfluorodecyltrimethoxysilane, 1H,1H,2H,2H-perfluorodecyltriethoxysilane and 1H,1H,2H,2H-perfluorodecyltrichlorosilane.

[0024] Furthermore, the step of etching with an acid solution comprises:

[0025] Soak the glass fiber in an acid solution and react at 40-60°C for 2-3 hours;

[0026] The acidic solution is a dilute sulfuric acid solution, a dilute hydrochloric acid solution, or a mixture of the two. The concentration of the dilute sulfuric acid solution or the dilute hydrochloric acid solution is 0.05-0.2 mol / L.

[0027] Furthermore, the glass fiber has a length of 50-150 μm and a diameter of 8-10 μm.

[0028] In a second aspect, the present application provides a modified glass fiber, wherein the modified glass fiber is prepared by the preparation method of the modified glass fiber as described in the first aspect.

[0029] In a third aspect, the present application provides a PFA composite material, wherein the raw materials include the following components calculated by mass percentage:

[0030] 15-25% of the modified glass fiber as described in the second aspect, 2-5% of the lubricating phase, and the balance of PFA powder;

[0031] The lubricating phase is one or more of graphite, molybdenum disulfide and tungsten disulfide.

[0032] In a fourth aspect, the present application provides a method for preparing the PFA composite material as described in the third aspect, comprising the following steps:

[0033] The modified glass fiber, lubricating phase and PFA powder are mixed according to a proportion, and then injection-molded into a mold, and cooled to obtain the PFA composite material;

[0034] The injection molding temperature is 350-365°C, the injection time is 15-25 min, the pressure is 0.5-0.7 MPa, and the mold temperature is 210-230°C.

[0035] Beneficial effects: Through the preparation method provided in the present application, the glass fiber surface is roughened and then coated with an organic resin layer. The organic resin layer has excellent elastic modulus and heat resistance, and can form a porous organic interface layer. The addition of perfluorosilane can improve the interface lubricity, which can help to melt and mechanically anchor with PFA, comprehensively improve the phase separation problem during blending and doping of traditional composite materials, and can also significantly improve the mechanical properties of glass fiber reinforced PFA composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a stress-strain schematic diagram of the products of Examples 1-3 and Comparative Examples 1-3 of the present application.

[0037] Figure 2 This is a three-dimensional image of the wear scar of the product of Example 1 of the present application.

[0038] Figure 3 This is a three-dimensional image of the wear scar of the product of Example 2 of the present application.

[0039] Figure 4 This is a three-dimensional image of the wear scar of the product of Example 3 of the present application.

[0040] Figure 5 This is a three-dimensional diagram of the wear scar of the product of comparative example 1 of the present application.

[0041] Figure 6 This is a three-dimensional diagram of the wear scar of the product of comparative example 2 of the present application.

[0042] Figure 7 This is a three-dimensional diagram of the wear scar of the product of comparative example 3 of the present application. DETAILED DESCRIPTION

[0043] The present application provides a modified glass fiber, PFA composite material and a preparation method thereof. To make the purpose, technical solution and effect of the present application clearer and more specific, the present application is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0044] The present application provides a method for preparing a modified glass fiber, which comprises the following steps:

[0045] S1, desizing the glass fiber, etching it with an acid solution, washing it to neutrality and drying it to obtain activated glass fiber;

[0046] S2, preparing resin reaction solution;

[0047] S3, adding perfluorosilane and activated glass fiber into the resin reaction solution and stirring, then separating the activated glass fiber and performing heat treatment to obtain modified glass fiber.

[0048] Through the preparation method provided in the present application, the glass fiber surface is roughened and then coated with an organic resin layer. The organic resin layer has excellent elastic modulus and heat resistance, and can form a porous organic interface layer. The addition of perfluorosilane can improve the interface lubricity, which can help to melt and mechanically anchor with PFA, comprehensively improve the phase separation problem during blending and doping of traditional composite materials, and can also significantly improve the mechanical properties of glass fiber reinforced PFA composite materials.

[0049] Specifically, in the present application, the modified glass fiber is prepared by adopting the form of surface coating bonding, wherein the degree of bonding between the glass fiber and the resin layer is high, and no separation of the resin layer occurs during ultrasonic vibration in ethanol. The modified glass fiber has a certain bonding force and can be used as a reinforcing phase of a fluorine-based composite material with a good reinforcing effect.

[0050] Furthermore, in step S1, the length of the glass fiber is 50-150 μm and the diameter is 8-10 μm. In the present application, by controlling the specifications of the selected glass fiber within a suitable range, the reinforcing effect on the fluorine-based material is better, while avoiding the aspect ratio being too large so as to prevent it from falling off from the matrix.

[0051] Specifically, in step S1, the desizing can be performed by placing the glass fiber in a muffle furnace and subjecting the glass fiber to a high temperature treatment at 350° C. to 450° C. for 2 to 4 hours.

[0052] Furthermore, in step S1, the step of etching by an acid solution includes:

[0053] Soak the glass fiber in an acid solution and react at 40-60°C for 2-3 hours;

[0054] The acidic solution may be a dilute sulfuric acid solution, a dilute hydrochloric acid solution, or a mixture of the two, and the concentration of the dilute sulfuric acid solution or the dilute hydrochloric acid solution is 0.05-0.2 mol / L.

[0055] In the present application, the acidic solution can micro-etch the glass fiber to increase the silicon-oxygen reaction activity on the surface of the glass fiber so as to modify it and improve the bonding effect with the formed resin layer, while also avoiding structural collapse of the glass fiber and helping to maintain the reinforcement effect.

[0056] Specifically, the glass fiber is treated with appropriate acid or alkali, the purpose is to help improve the interface "anchoring effect" of the fiber and the polymer by the depression and micropore formed by surface etching, and the surface produces Si-OH with certain reactivity. However, its etching effect needs to be controlled. If a large amount of oxides on the surface are dissolved by a strong acid with high concentration, the glass fiber structure will inevitably collapse, which greatly reduces the strength of the glass fiber. In the present application, the etching treatment is used as a preliminary activation, and perfluorosilane needs to be introduced for the second step activation later. The ultimate goal is to improve the mechanical properties. If the preliminary activation etches the glass fiber severely, in addition to affecting its enhanced performance, it will also affect the binding effect of the second step activation. Therefore, in the present application, a dilute hydrochloric acid solution, a dilute sulfuric acid solution or a mixture of the two with a concentration of 0.05-0.2mol / L is used to treat 2-3h, which can make the etching effect more meet the requirements of the preparation of this material. Wherein the concentration of the dilute hydrochloric acid solution or the dilute sulfuric acid solution is preferably 0.1mol / L, and the treatment time is preferably 2h.

[0057] Furthermore, in step S2, the step of preparing the resin reaction solution includes:

[0058] S21, adding a diamine monomer and a dianhydride monomer into a solvent, and reacting under nitrogen protection to obtain a precursor solution;

[0059] S22, adding dibutyl phthalate into the precursor solution and mixing to obtain a resin reaction solution.

[0060] In the present application, by adding dibutyl phthalate (DBP), during the stirring process, dibutyl phthalate is dispersed in the resin reaction liquid, and the separated activated glass fiber is wrapped by the resin reaction liquid. In the subsequent heat treatment, while the precursor is imidized to form a resin layer, the dibutyl phthalate therein is volatilized during the heat treatment and acts on the resin layer, increasing the roughness of the resin layer, thereby obtaining a porous resin layer, increasing the specific surface area, and helping to improve the bonding degree between the modified glass fiber and the resin matrix, which can effectively slow down the occurrence of phase separation.

[0061] Further, in step S21, the mass of the precursor generated by the reaction of the diamine monomer and the dianhydride monomer is 10-13% of the mass of the solvent. Specifically, the precursor generated by the copolymerization of the diamine monomer and the dianhydride monomer is polyamic acid.

[0062] In the present application, since the activated glass fiber will be filtered and separated after the reaction with the resin reaction liquid is completed, there is only a very thin resin layer on the surface of the activated glass fiber, which requires the precursor to have a certain fluidity and a certain viscosity. When the precursor concentration is too low, the precursor cannot well infiltrate the activated glass fiber, and the final material is difficult to achieve the required strength. However, when the precursor concentration is too high, more monomer raw materials are required, which dissolves slowly and is difficult to control during the reaction. In addition, the reaction liquid will be too thick, and the operation will be difficult to control during filtration. It is easy to be excessively enriched on the surface of the activated glass fiber. After subsequent heat treatment, the thicker resin layer formed will cause the material strength to decrease due to stress concentration.

[0063] Specifically, the amounts of diamine monomer and dianhydride monomer can be controlled to ensure that the polyamic acid generated by the complete reaction is in the required amount, and the molar ratio of diamine monomer to dianhydride monomer can be controlled to be 1:1.

[0064] Furthermore, the diamine monomer may be one or more of 2,2'-bis(trifluoromethyl)diaminobiphenyl (TFMB), 4,4'diaminodiphenyl ether (ODA), p-phenylenediamine (PDA), and 2-(4-aminophenyl)-5-aminobenzimidazole (BIA);

[0065] The dianhydride monomer may be one or more of 4,4'-diphenyl ether tetracarboxylic dianhydride (ODPA), 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA), 3,3',4,4'-biphenyl tetracarboxylic dianhydride (BPDA), and hexafluoroisopropylphthalic anhydride (6FDA).

[0066] Specifically, the solvent may be one or more of dimethylacetamide, dimethylformamide, and methylpyrrolidone.

[0067] Furthermore, in step S22, the mass proportion of dibutyl phthalate in the resin reaction liquid is 3-8%, preferably 5-8%.

[0068] Specifically, the present application uses dibutyl phthalate to cause pores in the resin, which can volatilize to form uniform and dense pores at a higher dosage. However, in the present application, the glass fiber surface is only covered with a very thin layer of resin. If the pore-causing effect is too high, defects are easily generated, which damages the resin layer and affects the subsequent anchoring effect. Therefore, the present application can control the pore structure distributed in the resin layer to an appropriate degree by controlling the dosage of dibutyl phthalate, improve the bonding ability of the resin layer while maintaining sufficient stability, and can be well bonded with the resin matrix after injection molding.

[0069] Furthermore, in step S3, the mass of activated glass fiber added is 10%-15% of the mass of the resin reaction liquid. Specifically, by controlling the activated glass fiber and the resin reaction liquid at a suitable mass ratio, it is beneficial to obtain a resin layer of suitable thickness on the surface so as to exert the bonding performance.

[0070] Furthermore, in step S3, the added mass of perfluorosilane is 2-3% of the mass of the activated glass fiber.

[0071] Specifically, the resin reaction liquid in step S3 includes dibutyl phthalate, and activated glass fiber and perfluorosilane are added. Perfluorosilane can produce a certain chemical bonding effect on the activated glass fiber and the resin reaction liquid after etching, and appropriately strengthen the anchoring of the glass fiber-resin surface; at this time, the addition of dibutyl phthalate does not participate in the reaction, and physically volatilizes during the subsequent heating treatment.

[0072] Among them, perfluorosilane is a fluorine-containing silane coupling agent that can form a covalent bond with Si-OH on the surface of activated glass fiber and form a "bridge" in the inorganic-polymer. Compared with other silane coupling agents, the selection of perfluorosilane takes into account the fluorine-based and hydrophobic properties of the matrix. The coupling agent can be modified in the form of direct addition of a small amount, so it is directly added to the activated glass fiber-resin reaction liquid system.

[0073] Specifically, in step S3, stirring can be performed by stirring at a constant speed for 1 h to 3 h to ensure that perfluorosilane and dibutyl phthalate are evenly dispersed in the resin reaction solution.

[0074] In the present application, the anchoring process of the activated glass fiber and the resin is first completed by stirring and mixing. Perfluorosilane can participate in the preliminary reaction and needs to be uniformly dispersed in the resin reaction liquid. When the addition amount is too low, it cannot effectively infiltrate the system. When the addition amount is too high, it cannot fully participate in the reaction and is easily accumulated on the surface of the glass fiber, isolating the coupling effect of each other. Therefore, the present application controls the addition amount of perfluorosilane to improve the anchoring effect between the activated glass fiber and the resin layer.

[0075] Furthermore, the perfluorosilane may be one or more of 1H,1H,2H,2H-perfluorodecyltrimethoxysilane, 1H,1H,2H,2H-perfluorodecyltriethoxysilane, and 1H,1H,2H,2H-perfluorodecyltrichlorosilane.

[0076] In the present application, the resin layer formed in the modified glass fiber will form a porous structure. While the specific surface area increases, the interface effect will also be improved. By controlling the selected perfluorosilane in an appropriate amount, the surface energy of the resin layer can also be reduced. While forming a porous structure with heating, the interfacial wettability of the resin layer is improved, which is beneficial to the subsequent anchoring and bonding with the resin matrix.

[0077] Specifically, in step S3, the activated glass fiber can be separated from the resin reaction solution by filtration.

[0078] Further, in step S3, the heat treatment step includes:

[0079] The activated glass fiber is kept at 80-150°C for 30-50 minutes, then at 150-220°C for 40-60 minutes, and finally at 280-340°C for 20-40 minutes.

[0080] Specifically, since the present application requires pore formation through volatilization of dibutyl phthalate, if rapid imidization is performed directly at the reaction temperature, the formed resin layer will be difficult to cooperate with the volatilization effect of dibutyl phthalate, which will affect the uniform refinement effect of the formed pore structure and further affect the anchoring effect.

[0081] In the present application, after the activated glass fiber is separated from the resin reaction liquid, in addition to the precursor, a certain amount of solvent remains. In the first stage, the glass fiber is kept at 80-150°C for 30-50 minutes, and most of the residual solvent evaporates to avoid affecting the subsequent pore-forming effect of dibutyl phthalate. At this time, dibutyl phthalate evaporates slowly and there is a slow imidization process. In the second stage, the glass fiber is kept at 150-220°C for 40-60 minutes, and the residual solvent continues to evaporate. The volatilization of dibutyl phthalate forms holes in situ, and the imidization is accelerated at this temperature. After most of the residual solvent is volatilized and imidization is slowly carried out in the first stage, the stability is first improved to avoid strength failure due to concentrated pore-forming effect in the unstable situation. Then, by accelerating the volatilization and imidization process of dibutyl phthalate, pores are volatilized while the main structure of the resin layer is formed, thereby improving the distribution effect of the pore structure. Finally, in the third stage, the temperature is kept at 280-340℃ for 20-40min. At this time, there is almost no solvent, the dibutyl phthalate basically completes the pore-forming effect, the imidization is also basically completed, and the resin layer forms a porous and flexible layer on the surface of the activated glass fiber.

[0082] Through the modified design of the preparation method of the present application, the prepared modified glass fiber can be adapted to fluororesins with high molding temperatures and harsh application conditions, can improve the phase separation phenomenon during the blending and doping of traditional composite materials, and significantly improve the mechanical properties of glass fiber reinforced PFA composite materials. Compared with the separability of glass fiber and PFA fluorine-based matrix, the surface of the prepared modified glass fiber has a transition layer. Because imidization occurs at any time, the present application uses dibutyl phthalate as a low-molecular plasticizer. By controlling the heat treatment process, in addition to being able to improve the formed pore performance, the volatilization process of dibutyl phthalate and the solvent together also helps the resin to change from a rubber state to a glass state during the imidization process. At a higher molding temperature of the composite material, the transition layer can be high-temperature anchored by melting the interface of the modified glass fiber-PFA, thereby improving the mechanical strength of the PFA material, and is specifically embodied in that the wear mark interface is rough and the wear marks are shallow, and the tensile strength is high.

[0083] The present application also provides a modified glass fiber, wherein the modified glass fiber is prepared by the above-mentioned preparation method of the modified glass fiber. The prepared modified glass fiber can be used as a reinforcing phase to reinforce the fluororesin composite material, so that it has better mechanical properties and heat resistance and wear resistance.

[0084] The present application also provides a PFA composite material, wherein the raw materials include the following components calculated by mass percentage:

[0085] 15-25% of the modified glass fiber as described above, 2-5% of the lubricating phase, and the balance of PFA powder.

[0086] The PFA composite material provided in the present application has good mechanical properties and heat and wear resistance. Through the interaction between the modified glass fiber and PFA, the PFA composite material has good bonding performance after preparation and can effectively deal with the problem of phase separation.

[0087] Specifically, if the glass fiber reinforcement phase, polyimide reinforcement phase, lubricating phase, and fluorine matrix are simply mixed, the interfacial bonding force is too weak to be used in practice. The modified glass fiber used in this application has been adjusted in performance, and the interfacial bonding force used as a reinforcement phase is strong, which can improve the problem of phase separation. Moreover, compared with other fluoropolymers such as PTFE (polytetrafluoroethylene), the PFA (tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer) selected in this application not only has a lower melting point but is also fusible, and can be formed by molding / extrusion molding and the like. More importantly, the fusible properties of PFA can produce a certain mechanical anchoring effect with the above-mentioned glass fiber coated with a porous resin layer in a molten state during the molding process, thereby improving the bonding problem of glass fiber reinforced fluororesin.

[0088] Furthermore, the lubricating phase is one or more of graphite, molybdenum disulfide, and tungsten disulfide. In the present application, the modified glass fiber used has a porous structure, and by selecting a solid lubricant with weak shear force, the bonding between the reinforcing phase and the resin matrix is ​​not affected too much, and the friction and wear performance can be further improved while effectively alleviating the phase separation problem.

[0089] Through the composite material and modified design provided in this application, the modified glass fiber can be adapted to fluororesins with high molding temperatures and harsh application conditions, comprehensively improve the phase separation phenomenon during blending and doping of traditional composite materials, and significantly improve the mechanical properties of glass fiber reinforced PFA composite materials.

[0090] The present application also provides a method for preparing the PFA composite material as described above, which comprises the following steps:

[0091] The modified glass fiber, the lubricating phase and the PFA powder are mixed according to a proportion, and then injection-molded into a mold, and cooled to obtain a PFA composite material;

[0092] The injection molding temperature is 350-365°C, the time is 15-25min, the pressure is 0.5-0.7MPa, and the mold temperature is 210-230°C.

[0093] The shape of the mold can be adjusted to obtain products of desired shapes, such as dumbbell-shaped, round, and the like.

[0094] The invention is further described below by means of specific examples.

[0095] Example 1

[0096] The raw materials of the PFA composite material of Example 1 include the following components calculated by mass percentage: 15% of the modified glass fiber (glass fiber reinforcement phase) of Example 1, 5% of molybdenum disulfide (lubricating phase), and the balance of PFA powder (matrix).

[0097] The method for preparing the modified glass fiber of Example 1 comprises the following steps:

[0098] (1) The glass fiber is placed in a muffle furnace and subjected to high-temperature treatment at 400°C for 2 h to remove the pulp. The glass fiber is then micro-etched with a 0.05 mol / L dilute hydrochloric acid solution for 3 h. The activated glass fiber is washed to neutrality and then dried for later use.

[0099] (2) Prepare the resin reaction liquid. Weigh 4,4'-diaminodiphenyl ether, 2-(4-aminophenyl)-5-aminobenzimidazole, and hexafluoroisopropylphthalic anhydride in a molar ratio of 6:4:10, and react in dimethylacetamide solvent under nitrogen protection for 6 hours to obtain a precursor solution. The mass of the precursor polyamic acid generated in the precursor solution accounts for 10% of the mass of the dimethylacetamide solvent. After the reaction is sufficient, add dibutyl phthalate and stir at a constant speed for 1 hour to obtain a resin reaction liquid. The mass of dibutyl phthalate in the resin reaction liquid accounts for 5%.

[0100] (3) 1H,1H,2H,2H-perfluorodecyltriethoxysilane and the activated glass fiber obtained in step (1) are added to the resin reaction solution obtained in step (2) and stirred at a constant speed for 1 hour. The activated glass fiber and the resin reaction solution are then separated, and the collected activated glass fiber is heat-treated to complete imidization of the resin layer on the surface of the glass fiber, thereby obtaining the modified glass fiber of Example 1. The amount of activated glass fiber added is 13% of the mass of the resin reaction solution, and the amount of perfluorosilane added is 3% of the mass of the activated glass fiber. The heat treatment step includes: keeping the activated glass fiber at 120°C for 30 minutes, then keeping it at 200°C for 60 minutes, and finally keeping it at 320°C for 20 minutes.

[0101] The preparation method of the PFA composite material of Example 1 comprises the following steps:

[0102] Calculated by mass percentage, 15% of the modified glass fiber of Example 1, 5% of molybdenum disulfide, and 80% of PFA powder were configured, and the raw materials were mixed according to the ratio and then injection-molded into a mold, and cooled to obtain the dumbbell-shaped and round PFA composite material products of Example 1. Among them, the injection molding temperature was 360°C, the injection molding time was 25min, the injection molding pressure was 0.5MPa, and the mold temperature during injection molding and extrusion was 230°C.

[0103] The dumbbell-shaped and circular PFA composite products prepared in Example 1 were subjected to tensile strength and wear tests.

[0104] Example 2

[0105] The raw materials of the PFA composite material of Example 2 include the following components calculated by mass percentage: 18% of the modified glass fiber (glass fiber reinforcement phase) of Example 2, 2% of graphite (lubricating phase), and the balance of PFA powder (matrix).

[0106] The method for preparing the modified glass fiber of Example 2 comprises the following steps:

[0107] (1) The glass fiber was placed in a muffle furnace and subjected to high-temperature treatment at 350°C for 3 h to remove the pulp. Then, a 0.1 mol / L dilute hydrochloric acid solution and a 0.1 mol / L dilute sulfuric acid solution were mixed in a volume ratio of 1:1 and the glass fiber was micro-etched for 2 h. The glass fiber was washed to neutrality and then dried to obtain activated glass fiber for later use.

[0108] (2) Prepare the resin reaction liquid. Weigh 2,2'-bis(trifluoromethyl)diaminobiphenyl, 2-(4-aminophenyl)-5-aminobenzimidazole, and 3,3',4,4'-biphenyltetracarboxylic dianhydride at a molar ratio of 7:3:10, and react in dimethylformamide solvent under nitrogen protection for 6 hours to obtain a precursor solution. The mass of the precursor polyamic acid generated in the precursor solution accounts for 13% of the mass of the dimethylformamide solvent. After the reaction is sufficient, add dibutyl phthalate and stir at a constant speed for 3 hours to obtain a resin reaction liquid. The mass proportion of dibutyl phthalate in the resin reaction liquid is 8%.

[0109] (3) 1H,1H,2H,2H-perfluorodecyltrichlorosilane and the activated glass fiber obtained in step (1) are added to the resin reaction solution obtained in step (2) and stirred at a constant speed for 1 hour. The activated glass fiber and the resin reaction solution are then separated, and the collected activated glass fiber is heat-treated to complete imidization of the resin layer on the surface of the glass fiber, thereby obtaining the modified glass fiber of Example 2. The amount of activated glass fiber added is 10% of the mass of the resin reaction solution, and the amount of perfluorosilane added is 2% of the mass of the activated glass fiber. The heat treatment step includes: keeping the activated glass fiber at 100°C for 50 minutes, then keeping it at 220°C for 50 minutes, and finally keeping it at 300°C for 40 minutes.

[0110] The preparation method of the PFA composite material of Example 2 comprises the following steps:

[0111] Calculated by mass percentage, 18% of the modified glass fiber of Example 2, 2% of graphite, and 80% of PFA powder were configured, and the raw materials were mixed according to the ratio and then injection-molded into a mold, and cooled to obtain the dumbbell-shaped and round PFA composite material products of Example 1. Among them, the injection molding temperature was 355°C, the injection molding time was 15min, the injection molding pressure was 0.6MPa, and the mold temperature during injection molding and extrusion was 220°C.

[0112] The dumbbell-shaped and circular PFA composite products prepared in Example 2 were subjected to tensile strength and wear tests.

[0113] Example 3

[0114] The raw materials of the PFA composite material of Example 3 include the following components calculated by mass percentage: 25% of the modified glass fiber (glass fiber reinforcement phase) of Example 3, 3% of tungsten disulfide (lubricating phase), and the balance of PFA powder (matrix).

[0115] The method for preparing the modified glass fiber of Example 3 comprises the following steps:

[0116] (1) The glass fiber is placed in a muffle furnace and subjected to high-temperature treatment at 450°C for 2 h to remove the pulp. The glass fiber is then micro-etched with a 0.2 mol / L dilute hydrochloric acid solution for 2 h. The activated glass fiber is washed to neutrality and then dried for later use.

[0117] (2) Prepare the resin reaction liquid. Weigh 4,4'-diaminodiphenyl ether, p-phenylenediamine, and 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride at a molar ratio of 5:5:10, and react in methyl pyrrolidone solvent under nitrogen protection for 4 hours to obtain a precursor solution. The mass of the precursor polyamic acid generated in the precursor solution accounts for 15% of the mass of the methyl pyrrolidone solvent. After the reaction is sufficient, add dibutyl phthalate and stir at a constant speed for 2 hours to obtain a resin reaction liquid. The mass proportion of dibutyl phthalate in the resin reaction liquid is 7%.

[0118] (3) 1H,1H,2H,2H-perfluorodecyltriethoxysilane and the activated glass fiber obtained in step (1) are added to the resin reaction solution obtained in step (2) and stirred at a constant speed for 2 hours. The activated glass fiber and the resin reaction solution are then separated, and the collected activated glass fiber is heat-treated to complete imidization of the resin layer on the surface of the glass fiber, thereby obtaining the modified glass fiber of Example 3. The added mass of the activated glass fiber is 15% of the mass of the resin reaction solution, and the added amount of perfluorosilane is 2% of the mass of the activated glass fiber. The heat treatment step includes: keeping the activated glass fiber at 80°C for 40 minutes, then keeping it at 180°C for 50 minutes, and finally keeping it at 310°C for 20 minutes.

[0119] The preparation method of the PFA composite material of Example 3 comprises the following steps:

[0120] Calculated by mass percentage, 25% of the modified glass fiber of Example 3, 3% of tungsten disulfide, and 72% of PFA powder were configured, and the raw materials were mixed according to the ratio and then injection-molded into a mold, and cooled to obtain the dumbbell-shaped and round PFA composite material products of Example 3. Among them, the injection molding temperature was 365°C, the injection molding time was 20min, the injection molding pressure was 0.7MPa, and the mold temperature during injection molding and extrusion was 220°C.

[0121] The dumbbell-shaped and circular PFA composite products prepared in Example 3 were subjected to tensile strength and wear tests.

[0122] Comparative Example 1

[0123] The composite material of Comparative Example 1 includes the following components in terms of weight percentage:

[0124] Unmodified glass fiber (glass fiber reinforcement phase) 20%, PFA matrix balance.

[0125] The preparation method of the composite material of Comparative Example 1 comprises the following steps:

[0126] Calculated by mass percentage, 20% unmodified glass fiber and 80% PFA powder were configured, and the raw materials were mixed according to the ratio and then injected into the mold for molding, and then cooled to obtain the dumbbell-shaped and round composite material products of Comparative Example 1. Among them, the injection molding temperature was 360°C, the injection molding time was 25min, the injection molding pressure was 0.5MPa, and the mold temperature during injection molding and extrusion was 230°C.

[0127] The dumbbell-shaped and circular composite products prepared in Comparative Example 1 were subjected to tensile strength and abrasion tests.

[0128] Comparative Example 2

[0129] The composite material of Comparative Example 2 includes the following components in terms of weight percentage:

[0130] Comparative Example 2: 18% of unactivated glass fiber (glass fiber reinforcement phase), 2% of graphite (lubricating phase), and the remainder of PFA matrix.

[0131] Wherein, the preparation method of the unactivated glass fiber of comparative example 2 comprises the following steps:

[0132] (1) The glass fiber is not treated.

[0133] (2) Prepare a resin reaction solution. Weigh three monomers, 2,2'-bis(trifluoromethyl)diaminobiphenyl, 2-(4-aminophenyl)-5-aminobenzimidazole, and 3,3',4,4'-biphenyltetracarboxylic dianhydride, at a molar ratio of 7:3:10, and react in dimethylformamide solvent under nitrogen protection for 6 hours to obtain a precursor solution. The mass of the precursor polyamic acid generated by the reaction in the precursor solution accounts for 13% of the mass of the dimethylformamide solvent, thereby obtaining a resin reaction solution of Comparative Example 2.

[0134] (3) Adding glass fiber directly to the resin reaction liquid obtained in step (2) and stirring at a constant speed for 3 hours, then separating the glass fiber from the resin reaction liquid, and subjecting the collected activated glass fiber to heat treatment, so that the resin layer on the surface of the glass fiber is imidized to obtain the non-activated glass fiber of Comparative Example 2. The mass of the activated glass fiber added is 10% of the mass of the resin reaction liquid, and the heat treatment step comprises: keeping the activated glass fiber at 100°C for 50 minutes, then keeping it at 220°C for 50 minutes, and finally keeping it at 300°C for 40 minutes.

[0135] The preparation method of the composite material of Comparative Example 2 comprises the following steps:

[0136] Calculated by mass percentage, 18% of the unactivated glass fiber of comparative example 2, 2% of graphite, and 80% of PFA powder were configured, and the raw materials were mixed according to the ratio and then injected into the mold for molding, and then cooled to obtain the dumbbell-shaped and round composite material products of comparative example 1. Among them, the injection molding temperature was 355°C, the injection molding time was 15min, the injection molding pressure was 0.6MPa, and the mold temperature during injection molding and extrusion was 220°C.

[0137] The dumbbell-shaped and circular composite products prepared in Comparative Example 2 were subjected to tensile strength and abrasion tests.

[0138] Comparative Example 3

[0139] The composite material of Comparative Example 3 includes the following components in terms of weight percentage:

[0140] Unmodified glass fiber (glass fiber reinforcement phase) 20%, polyimide powder 5%, tungsten disulfide (lubricating phase) 3%, PFA matrix balance.

[0141] The preparation method of the composite material of Comparative Example 3 comprises the following steps:

[0142] Calculated by mass percentage, 20% unmodified glass fiber, 5% polyimide, 3% tungsten disulfide, and 72% PFA powder are configured, and the raw materials are mixed according to the ratio and then injected into the mold for molding, and then cooled to obtain the dumbbell-shaped and round composite material products of comparative example 3. Among them, the injection molding temperature is 365°C, the injection molding time is 20min, the injection molding pressure is 0.7MPa, and the mold temperature during injection extrusion is 220°C.

[0143] The dumbbell-shaped and circular composite products prepared in Comparative Example 3 were subjected to tensile strength and abrasion tests.

[0144] The dumbbell-shaped products prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to mechanical property tests, and the round products were subjected to steel ball grinding in a friction tester to determine the mechanical properties of the composition. The stress-strain diagram of the products of Examples 1-3 and Comparative Examples 1-3 measured by a universal electronic testing machine is shown in the figure below: Figure 1 The three-dimensional white light interference diagrams of Examples 1-3 and Comparative Examples 1-3 after wear testing in a friction and wear testing machine are shown in Figure 1. Figure 2-Figure 7 As shown, the wear rate is calculated from this. The deeper the indentation in the three-dimensional graph, the greater the wear. The measured data is shown in Table 1:

[0145] Table 1

[0146] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Tensile strength / MPa 20.63 19.69 19.80 13.60 16.58 10.32 Elongation at break / % 321 342 364 275 360 258 <![CDATA[Wear rate * 10 -6 / (mm 3 / N.m)]]> 4.49 4.65 3.14 8.92 6.25 11.02

[0147] Phase separation will lead to deeper wear of the product. By comparing the test results, it can be seen that comparative example 1 uses a single glass fiber for matrix reinforcement. Due to the poor inorganic-organic interface bonding force, it shows lower strength and deeper wear. However, through the surface treatment of the glass fiber of Example 1 and the addition of the lubricating phase, the tensile strength is significantly improved, and the glass fiber-matrix interface forms an organic transition layer to participate in melting and play the role of anti-wear and friction reduction. Comparative example 2 adopts a simple coating form, so that the glass fiber and the surface coating layer have sufficient energy consumption and displacement during the fracture process, which is reflected in the increase of elongation at break and insufficient improvement of tensile strength, lack of mechanical interlocking ability. The tensile strength is improved by increasing the surface roughness of the glass fiber and adding interface additives in the preparation process of Example 2. Comparative example 3 directly uses glass fiber reinforcement phase, resin reinforcement phase, and lubricating phase to fill the matrix, and there is serious phase separation. Therefore, compared with Example 3 of the interface design, there is a situation of poor strength and high wear.

[0148] Through the interface modification method of the embodiment of the present application, the glass fiber reinforced fluororesin composite material has better mechanical properties and heat resistance and wear resistance, and effectively addresses the phase separation problem in the composite material.

[0149] It should be understood that the application of the present application is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made according to the above description, and all these improvements and changes should fall within the scope of protection of the present application.

Claims

1. A method for preparing modified glass fiber, characterized in that: The following steps are involved: The glass fiber is desized, and then etched with an acid solution, washed to neutrality, and then dried to obtain activated glass fiber; Preparing a resin reaction solution; adding perfluorosilane and the activated glass fiber into the resin reaction solution and stirring, separating the activated glass fiber and then performing heat treatment to obtain modified glass fiber; The step of configuring the resin reaction solution comprises: Adding diamine monomer and dianhydride monomer into a solvent, and reacting under nitrogen protection to obtain a precursor solution; Then, adding dibutyl phthalate into the precursor solution and stirring and mixing, to obtain the resin reaction solution; The mass of the precursor generated by the reaction of the diamine monomer and the dianhydride monomer is 10-13% of the mass of the solvent; The mass proportion of dibutyl phthalate in the resin reaction liquid is 5-8%; The heat treatment steps include: The activated glass fiber is first kept at 80-150° C. for 30-50 minutes, then kept at 150-220° C. for 40-60 minutes, and finally kept at 280-340° C. for 20-40 minutes.

2. The method for preparing modified glass fiber according to claim 1, characterized in that: The diamine monomer is one or more of 2,2'-bis(trifluoromethyl)diaminobiphenyl, 4,4'-diaminodiphenyl ether, p-phenylenediamine, and 2-(4-aminophenyl)-5-aminobenzimidazole; The dianhydride monomer is one or more of 4,4'-diphenyl ether tetracarboxylic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, and hexafluoroisopropylphthalic anhydride; The solvent is one or more of dimethylacetamide, dimethylformamide and methyl pyrrolidone.

3. The method for preparing modified glass fiber according to claim 1, characterized in that: The added mass of the activated glass fiber is 10-15% of the mass of the resin reaction solution; The added mass of the perfluorosilane is 2-3% of the mass of the activated glass fiber; The perfluorosilane is one or more of 1H,1H,2H,2H-perfluorodecyltrimethoxysilane, 1H,1H,2H,2H-perfluorodecyltriethoxysilane and 1H,1H,2H,2H-perfluorodecyltrichlorosilane.

4. The method for preparing modified glass fiber according to claim 1, characterized in that: The step of etching with an acid solution comprises: Soak the glass fiber in an acid solution and react at 40-60°C for 2-3 hours; The acidic solution is a dilute sulfuric acid solution, a dilute hydrochloric acid solution, or a mixture of the two. The concentration of the dilute sulfuric acid solution or the dilute hydrochloric acid solution is 0.05-0.2 mol / L.

5. The method for preparing modified glass fiber according to claim 1, characterized in that: The glass fiber has a length of 50-150 μm and a diameter of 8-10 μm.

6. A modified glass fiber, characterized in that: The modified glass fiber is prepared by the preparation method of any one of claims 1 to 5.

7. A PFA composite material, characterized in that: Calculated by mass percentage, the raw materials include the following components: 15-25% of the modified glass fiber as claimed in claim 6, 2-5% of the lubricating phase, and the balance of PFA powder; The lubricating phase is one or more of graphite, molybdenum disulfide and tungsten disulfide.

8. A method for preparing the PFA composite material as claimed in claim 7, characterized in that: The following steps are involved: The modified glass fiber, lubricating phase and PFA powder are mixed according to a proportion, and then injection-molded into a mold, and cooled to obtain the PFA composite material; The injection molding temperature is 350-365°C, the injection time is 15-25 min, the pressure is 0.5-0.7 MPa, and the mold temperature is 210-230°C.

Citation Information

Patent Citations

  • Long-fiber-reinforced thermoplastic resin preform and fiber-reinforced resin compact using same

    CN103974811A

  • Glass fiber with high heat resistance and preparation method thereof

    CN112624621A